2016
DOI: 10.1080/1828051x.2016.1147930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an e-nose ability to detect biogas plant efficiency: a case study

Abstract: The demand for online monitoring and control of biogas process is increasing, since better monitoring and control system can improve process plants stability and economy. A number of parameters in both the liquid and the gas phase have been suggested as process indicators (pH, alkalinity, VFA and H 2, redox potential, biogas production rate, biogas composition, FOS/TAC ratio, COD and/or VS reduction). The present study proposes the use of complex sensors as a possible solution to engineer a consistent control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This work showed that gas phase relation with anaerobic process should be deeper investigated, as an EN could indicate the reactor state, focusing on the gas phase. Similar conclusions can be drown from Costa et al [183] Orzi et al [184] investigate the correlation between microbial activity (i.e., biological stability measured by aerobic OD 20 test and ABP anaerobic tests) and odor emissions from municipal solid waste during anaerobic digestion in a full-scale treatment plant considering the three stages of the process (input, digested and post-digested waste). Authors used complementary approaches for the measurement of odor impact (olfactometry) and characterization of the different groups of VOCs responsible for that odor (GC-MS and PEN2 e-nose from Airsense).…”
Section: Anaerobic Digestion-biogas Formationmentioning
confidence: 54%
“…This work showed that gas phase relation with anaerobic process should be deeper investigated, as an EN could indicate the reactor state, focusing on the gas phase. Similar conclusions can be drown from Costa et al [183] Orzi et al [184] investigate the correlation between microbial activity (i.e., biological stability measured by aerobic OD 20 test and ABP anaerobic tests) and odor emissions from municipal solid waste during anaerobic digestion in a full-scale treatment plant considering the three stages of the process (input, digested and post-digested waste). Authors used complementary approaches for the measurement of odor impact (olfactometry) and characterization of the different groups of VOCs responsible for that odor (GC-MS and PEN2 e-nose from Airsense).…”
Section: Anaerobic Digestion-biogas Formationmentioning
confidence: 54%
“…MOS sensors are some of the most commonly used gas sensors for constructing sensor arrays due to their cost-effectiveness, reliability, and availability. They have been widely applied in agriculture and forestry industries for diagnosis of plant infection caused by fungus, bacteria, and viruses; insect damage; or mechanical damage [ 42 , 43 , 44 , 45 , 46 , 47 ]. The main advantages of MOS sensors are the fast response and recovery times, which mainly depend on the temperatures and the level of interaction between the sensors and gases [ 48 ].…”
Section: Electronic Nose Detecting Technologymentioning
confidence: 99%
“…Our design uses cheaper hardware and simple fuzzy logic algorithms compared to the complex pattern recognition (requiring training) algorithms. However, our method lacks the fine tuning achieved by other researchers [45].…”
Section: Photovoltaics Systemmentioning
confidence: 99%
“…Figure 18 shows actual display readings for the photovoltaics system. [45] is based on the e-nose. The e-nose whose design is premised on the biological method is capable of sensing a large number of gases through pattern recognition and is able to evaluate the stability of the digester [45].…”
Section: Photovoltaics Systemmentioning
confidence: 99%